Public Private Partnerships in the Caribbean : Bridging the Financing Gap - Guasch, Jose Luis (World Bank, Washington, DC, 2014)
Caribbean countries are committed to achieving significant economic and social development to raise the living standards and welfare of citizens. To achieve rapid development, to support most needed sustainable high growth rates and poverty reduction, it is necessary to make substantial and immediate investments in economic and social infrastructure. Efficient, cost competitive facilities and services in transport and communications, energy, water, sanitation, health and education are essential to drive and support this development effort and to reduce poverty. Yet, fiscal space, the resources available to the public sector for needed infrastructure investments are very limited. Many Caribbean countries have high levels of public debt as a percentage of gross domestic product (GDP) and high fiscal deficits. Under traditional public procurement, government obtains a public infrastructure service such as electricity, water supply, schools and hospitals, by engaging a contractor to construct a facility which the Government then owns, manages and operates. This form of public procurement will continue, but as a result of the limited fiscal space, public infrastructure services development will also be sought through public private partnership (PPP) arrangements which will mean a broader role for the private sector in providing infrastructure facilities and services. The Governments of most Caribbean countries appear fully committed to promoting economic activities and enhancing the well-being of its citizens through more active participation of the private sector in improving the infrastructure of the nation. Those Governments believe that improving infrastructure through PPP arrangements will harness the development of the private sector to contribute to the growth of GDP and poverty reduction over the life of their respective strategic development plan and current administrations.